Effect of Surfactants\ Tail Number on the PVDF/GO/TiO2-Based Nanofiltration Membrane for Dye Rejection and Antifouling Performance Improvement - Suriani Abu Bakar (Tanjung Malim, 2021)
Effect of Surfactants\ Tail Number on the PVDF/GO/TiO2-Based Nanofiltration Membrane for Dye Rejection and Antifouling Performance Improvement by Suriani Abu Bakar